TECHNICAL EDUCATION: FOR THE BENEFIT OF REGIONS, FOR THE BENEFIT OF THE COUNTRY - Nikolay D. Tskhadaya (Moscow Polytechnic University, 2016)
The article analyzes a role of technical education in technological and economic development of regions of Russia on the example of activity of USTU. The prerequisites allowing higher education institution to reach the status of basic regional university are submitted. The author considers an organic inclusiveness of higher education institution in the structure of the regional economy as the most actual advantage.